2016
DOI: 10.1159/000447307
|View full text |Cite
|
Sign up to set email alerts
|

Neighbourhood Determinants of Caries Experience in Preschool Children: A Multilevel Study

Abstract: Objectives: To investigate the association between neighbourhood factors and decayed, missing, and filled teeth (dmft) index among preschool children. Methods: The sample of this cross-sectional study comprised 1,110 children (0-5 years old) clustered in 16 official neighbourhoods of Canoas city, southern Brazil. Multilevel binomial models were used to estimate the association of contextual variables at neighbourhood level (Human Development Index, average income, and public primary health care units) with two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 37 publications
3
17
1
1
Order By: Relevance
“…Therefore, the social and cultural factors in which the individual is included would affect outcomes in oral health [Slade et al, 1996] and may differ between municipalities. In addition, individuals residing in more economically developed areas may have more opportunity of being treated [Priesnitz et al, 2016]. Thus, the decentralization of dental services should be prioritized in order to reduce the inequality in oral health among municipalities.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the social and cultural factors in which the individual is included would affect outcomes in oral health [Slade et al, 1996] and may differ between municipalities. In addition, individuals residing in more economically developed areas may have more opportunity of being treated [Priesnitz et al, 2016]. Thus, the decentralization of dental services should be prioritized in order to reduce the inequality in oral health among municipalities.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the importance of the neighborhood for general health and mortality outcomes has attracted increasing interest [Meijer et al, 2013;Diez Roux et al, 2016;Priesnitz et al, 2016]. Corresponding circumstances regarding dental health might be expected, as the distribution and severity of dental caries vary considerably between different countries and within the same country or region [Pitts et al, 2011;Coles et al, 2017].…”
Section: Introductionmentioning
confidence: 99%
“…Individual socioeconomic issues are associated with the occurrence of dental caries. Some studies have also found a relationship between dental caries and contextual factors. A child's surrounding environment can exert an influence on oral health, since individuals who live in the same context tend to exhibit similar behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…The school at which a child studies can be used as an indicator of socioeconomic status and is considered a viable predictor of caries experience in epidemiological studies conducted in Brazil. Studies have been conducted to analyse the influence of individual and contextual determinants on oral health. However, studies involving multilevel analyses on dental caries among 5‐year‐old children have limitations related to the sample.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation